HUBUNGAN PERILAKU MEROKOK PEMINUM KOPI DENGAN GINGIVITIS PADA MASYARAKAT DI BANTARAN SUNGAI MARTAPURA DESA MALI-MALI KABUPATEN BANJAR - yudhistira, putra anugrah; habibah, siti sabatul; sari, emilda (JURNAL TERAPIS GIGI DAN MULUT, 2022)
According to Ministry of Health Data, smoking prevalence has increased thrice since1995, from 7,1% to 20,5% in 2014. Periodontal disease is a condition that begins with gingivalinflammation and progresses to include damage to the tissue that supports teeth. Because itcontains hazardous compounds such as tar, nicotine, and carbon monoxide, smoking has aneffect on the proper function of the soft tissue cells of the gums.The goal of this study is to see if there’s a link between coffee users’s smoking habitsand gingivitis in the Mali-Mali Village, Banjar Regency community on the banks of the MartapuraRiver. An analytic survey with a Cross Sectionnal research design is this sort of study.Purposive Sampling was used with a sample of 50 respondents. The Chi-Square Test was usedto analyze the data.The findings revealed that smoking behavior fell into the category of moderate smokers,with the majority of them suffering from mild gingivitis. The p-value (0,000) with alpha (0,05) wascalculated using the Pearson Chi-Square test results, indicating that Ho is rejected and Ha isaccepted. This suggests that there is a link between coffee users’ smoking habits and gingivitisin the Mali-Mali Village Banjar Regency community on the banks of the Martapura River.This conclusion is that there is a link between coffee users’s smoking habits andgingivitis in the Mali-Mali Village Banjar district, located on the banks of the Martapura River. Toprevent gingivitis, it is recommended that people quit smoking at young age for their health,especially their dental and oral health.